Daily volatility analysis of ISE - Tatlı, Serhat Zafer (My University, 2000)
It is generally accepted that financial market volatility is a very important criterion in investment decisions. Besides, it is also accepted that Turkey is one of the most important emerging countries throughout the world economy. When these two facts came together, they constructed the main aim of this study. This study aims to analyze the daily return volatility of ISE in TL and US $. By doing so, we try to find the most efficient econometric technique in modeling daily return volatility of ISE/ TL, and ISE/ $. In addition to this, the impacts of political, natural, and macroeconomic news effects are also analyzed. In daily level, ISE return volatility may be influenced by public announcements, i.e. monthly inflation rate announcements by SIS, political events, i.e. elections, and natural events, i.e. earthquake. 3131 observations for ISE/ TL, and 3107 observations for ISE/ $ between the dates of 26/ 10/ 1987 and 1/ 6/ 2000 are used in order to estimate the daily return volatility of ISE. This study reveals three important findings. First, ISE daily return volatility exhibits conditional heteroskedasticity which is estimated by Arch-type models. Second, there is no asymmetric news effects. This means that the hypothesis that bad news have a greater impact on volatility than good news is not acceptable. And finally, expected news arrivals like public announcements are much more effective than the unexpected news arrivals like natural events.
Keywords: Borsa; İstanbul (Türkiye)_Borsa